POLA PENEGAKAN HUKUM TERHADAP INKONSISTENSI PEMERINTAH DALAM PENGAWASAN REKLAMASI PASCATAMBANG MINERAL DAN BATUBARA DI INDONESIA - Eli Tri Kursiswanti; Helmi; Ahmad Hambali (Collegium Studiosum Journal, 2026)
Mineral and coal mining activities in Indonesia frequently leave serious environmental problems, particularly regarding the failure to implement post-mining reclamation. Although regulations strictly govern this obligation, field realities show inconsistency on the part of the government in supervision and law enforcement, opening loopholes for corporations to neglect land rehabilitation obligations. This article aims to (1) map the pattern of law enforcement applied to violations of post-mining reclamation obligations, (2) identify the factors causing weak professionalism and consistency of officials in carrying out supervisory functions, and (3) formulate an ideal law enforcement reconstruction model. This study employs a Socio-Legal Studies approach combined with a Systematic Literature Review (SLR) of primary, secondary, and tertiary legal materials. The findings indicate that law enforcement of reclamation obligations remains partial and selective, influenced by overlapping central-regional authority, weak deterrent effects of administrative sanctions, and limited transparency in the Reclamation Guarantee (Jamrek) mechanism. As a contribution, this article proposes a "Consistent-Restorative" law enforcement model that integrates administrative legal certainty with restorative justice principles and public participation as a check-and-balance mechanism.